2015
DOI: 10.1371/journal.pone.0141371
|View full text |Cite
|
Sign up to set email alerts
|

Do Healthy Monarchs Migrate Farther? Tracking Natal Origins of Parasitized vs. Uninfected Monarch Butterflies Overwintering in Mexico

Abstract: Long-distance migration can lower parasite prevalence if strenuous journeys remove infected animals from wild populations. We examined wild monarch butterflies (Danaus plexippus) to investigate the potential costs of the protozoan Ophryocystis elektroscirrha on migratory success. We collected monarchs from two wintering sites in central Mexico to compare infection status with hydrogen isotope (δ 2H) measurements as an indicator of latitude of origin at the start of fall migration. On average, uninfected monarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 62 publications
(80 reference statements)
4
69
0
Order By: Relevance
“…Consistent with previous studies [26, 28, 30, 31], our results showed that monarchs that migrated the farthest distance on average from natal grounds to wintering sites had the longest and largest wings. This observation suggests that migration acted as a selective episode on monarch butterfly wing morphology, specifically on wing length and area, and this relationship did not arise from temperature-dependent effects on wing morphology.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with previous studies [26, 28, 30, 31], our results showed that monarchs that migrated the farthest distance on average from natal grounds to wintering sites had the longest and largest wings. This observation suggests that migration acted as a selective episode on monarch butterfly wing morphology, specifically on wing length and area, and this relationship did not arise from temperature-dependent effects on wing morphology.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, Dockx [27] showed that among monarchs captured in Cuba, migrants originating from northern latitudes had more angular wings than those identified as year-round residents. In more recent work, however, Li et al [28] found no difference in wing shape among monarchs from migratory versus non-migratory populations, and Altizer et al [30] also found no relationship between wing shape and estimated migration distance among eastern North American migrants. Thus, evidence for selection operating on wing shape in migratory monarchs appears to be mixed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Care was taken to remove only wing membrane and to avoid wing veins in the sample. Thus, our sample was designed to test for isotopic measurement the effects of natal origin on parasite loads (Altizer et al 2015), the role of wing coloration in flight distance (Hanley et al 2013) and general conservation concerns related to where most individuals are being produced (Flockhart et al 2017). Such tracking studies have used continental patterns, or isoscapes, of both precipitation δ 2 H and milkweed δ 13 C. Despite the demonstrated value of stable isotope measurements of butterfly wings to investigate migration, to our knowledge, there has been no previous investigation into the isotopic variance among different regions of wing material (primarily chitin) despite the fact that monarch wings, as with those of many lepidopterans, are highly variable in pigmentation.…”
Section: The Samplementioning
confidence: 99%
“…The measurement of δ 2 H in complex organic materials is challenging since a significant proportion of weakly bonded hydrogen can exchange with hydrogen from ambient water vapor. This effect can be controlled for by using the comparative equilibration approach employed here or use of modified carousel systems Meier-Augenstein et al 2013, Wassenaar et al 2015. Orange coloration is caused by the differential deposition of color pigments such as pterins and ommochromes on to wing scales Janssen et al 2001).…”
mentioning
confidence: 99%